United States : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that the U.S. economy's momentum in the first quarter of 2015 was sapped by unfavorable weather, a sharp contraction in oil sector investment, and the West Coast port strike. But the underpinnings for a continued expansion remain in place. A solid labor market, accommodative financial conditions, and cheaper oil should support a more dynamic path for the remainder of the year. Despite this, the weaker outturn in the first few months of 2015 will unavoidably pull down 2015 growth. Despite important policy uncertainties, the near-term fiscal outlook has improved, and the federal government deficit is likely to move modestly lower in the current fiscal year.